Społeczne konstruowanie percepcji. Argument przeciwko możliwości prywatnego postrzegania - Chmielewski, Adam
The subject of this article is a critical assessment of Alvin I. Goldman’s theory of perception which constitutes a part of his social epistemology. I argue that although perception is an important part of traditional epistemology, its social dimension in Goldman’s social epistemology is negligible and, as a result, his theory of perception remains indelibly individualistic and thus deficient. In opposition to such an understanding of perception, I develop an alternative view which enables one to understand perception as endowed with much broader social dimensions. To do so, I employ selected insights from the contemporary theory of perception and claim that individual perceptive faculties are inescapably exposed to various influences that contribute not only to their contents but also, more importantly, play a crucial role in the emergence and development of perceptive abilities in the first place. Relying on the discussion of Wittgenstein’s early views on perception, and his idea of the captivating effect of a picture, I argue that by practicing the art of seeing and understanding a picture we master the rules of sensory orders, or perceptual regimes, which are sustained by a collective perceptual hysteresis, and which enable us to see the world in a specifically ordered way. I also claim that though the sense of sight is a natural human endowment, the ability to see, like many other abilities, needs to be learned through a process which I call ‘seeing-with-others’. Since all cognitive subjects unavoidably take part in the creation of perceptual regimes – though they engage in the process to a varying degree – such interactive processes may be interpreted as democratic, though not in the consensual but rather in an agonistic sense.
Keywords: estetyka polityczna; histereza postrzegawcza; postrzeganie aspektowe; reżim postrzegania